Aquaporin 5 maintains lens transparency by regulating the lysosomal pathway using circRNA. Issue 6 (23rd February 2023) - Shaohua, Hu; Yihui, Wang; Kaier, Zhang; Ying, Bai; Xiaoyi, Wang; Hui, Zhao; Guohu, Di; Peng, Chen
Abstract: The lens is transparent, non‐vascular, elastic and wrapped in a transparent capsule. The lens oppacity of AQP5 −/− mice was increased more than that of wild‐type (AQP5 +/+ ) mice. In this study, we explored the potential functional role of circular RNAs (circRNAs) and transcription factor HSF4 in lens opacity in aquaporin 5 (AQP5) knockout (AQP5 −/− ) mice. Autophagy was impaired in the lens tissues of AQP5 −/− mice. Autophagic lysosomes in lens epithelial cells of AQP5 −/− mice were increased compared with AQP5 +/+ mice, based on analysis by transmission electron microscopy. The genetic information of the mice lens was obtained by high‐throughput sequencing, and then the downstream genes were analysed. A circRNA‐miRNA‐mRNA network related to lysosomal pathway was constructed by the bioinformatics analysis of the differentially expressed circRNAs. Based on the prediction of the TargetScan website and the validation by dual luciferase reporter assay and RNA immunoprecipitation‐qPCR, we found that circRNA (Chr16: 33421321‐33468183+) inhibited the function of HSF4 by sponging microRNA (miR‐149‐5p), and it downregulated the normal expression of lysosome‐related mRNAs. The accumulation of autophagic lysosome may be one of the reasons for the abnormal development of the lens in AQP5 −/− mice.